Microbial Transformation of neo-Clerodane Diterpenoid, Scutebarbatine F, by Streptomyces sp. CPCC 205437 - Zhang, Dewu; Tao, Xiaoyu; Gu, Guowei; Wang, Yujia; Zhao, Wenxia; Zhao, Wuli; Ren, Yan; Dai, Shengjun; Yu, Liyan (Frontiers in Microbiology, 2021)
Biotransformation of the neo-clerodane diterpene, scutebarbatine F (1) by Streptomyces sp. CPCC 205437 was investigated for the first time, which led to nine new metabolites, scutebarbatine F1F9 (210). Their structures were determined by extensive HRESIMS and NMR data analyses. The occurred reactions included hydroxylation, acetylation, and deacetylation. Compounds 24, 810 possess 18-OAc fragment, which were the first examples of 13-spiro neo-clerodanes with 18-OAc group. Compounds 710 were the first report of 13-spiro neo-clerodanes with 2-OH. Compounds 110 were biologically evaluated for the cytotoxic, antiviral, and antibacterial activities. Compounds 5, 7, 9 exhibited cytotoxic activities against H460 cancer cell line with inhibitory ratios of 46.0, 42.2, and 51.1 % at 0.3 μM. Compounds 5 displayed significant anti-influenza A virus activity with inhibitory ratio of 54.8 % at 20 μM, closed to positive control, ribavirin.